2017
DOI: 10.31235/osf.io/vzphs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Work-to-Family Enrichment and Gender Inequalities in Eight European Countries

Abstract: All social roles have positive and rewarding as well as negative or problematic aspects. Research on the work-family interface has predominantly focused on conflicting roles. In contrast, this paper extends research on work-family enrichment (WFE), a positive aspect of work, and gender differences in WFE in a cross-national context. Drawing upon social role theory and the culture sensitive theory on work-family enrichment, we examined gender differences in experiences of developmental WFE in a sample of servic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Once they reached home, they were bound to do house chores, further limiting their sunlight exposure time. Similar experiences were shared by women in eight European countries, whereby gender inequality and expectations of married working women, especially mothers, are higher in balancing work-family commitments compared to their counterparts [ 39 ].…”
Section: Discussionmentioning
confidence: 84%
“…Once they reached home, they were bound to do house chores, further limiting their sunlight exposure time. Similar experiences were shared by women in eight European countries, whereby gender inequality and expectations of married working women, especially mothers, are higher in balancing work-family commitments compared to their counterparts [ 39 ].…”
Section: Discussionmentioning
confidence: 84%
“…The reason for this interaction effect may be because of the difference in the salience of the family domain attached by the groups of managers. Women draw greater satisfaction from family life than from their work (Beham et al , 2017; Grzywacz and Marks, 2000; Rothbard, 2001) because of prevalent cultural values. Likewise, women are more likely to experience more satisfaction in family life when they are married than men because of widespread cultural norms and beliefs, particularly in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Considering how men and women define themselves and behave, arguably gender will moderate the effect of WFC and FS on millennial managers' engagement. Extant studies have shown that women value family more than men (Beham et al, 2017;Grzywacz and Marks, 2000). Lyu and Fan (2020) contend that men may be inclined to fulfil their family responsibilities through work.…”
Section: Moderating Effect Of Gender and Marital Statusmentioning
confidence: 99%
“…Research has shown that both male and female workers can transfer resources from their work role to their families through WFE (e.g., Beham, Drobni c, Pr€ ag, Baierl & Lewis, 2020;Schnettler et al, 2022). Yet work-family experiences can differ for men and women due to structural work conditions and traditional gender role demands.…”
Section: Mother's Satisfaction With Family Lifementioning
confidence: 99%